Computed tomographic features of lesions detected in horses with tarsal lameness. (16th July 2013) - Raes, E.; Bergman, H. J.; Van Ryssen, B.; Vanderperren, K.; Stock, E.; Saunders, J. H.
Summary Reasons for performing study Tarsal pain is a common cause of hindlimb lameness in horses. Diagnosis can usually be made with radiography and ultrasonography; however, in some cases, these techniques are inconclusive and additional imaging is necessary. No studies describing computed tomography (CT) features of different tarsal lesions in horses with tarsal lameness are reported. Objectives Our aims were as follows: 1) to characterise CT abnormalities in horses with tarsal lameness; 2) to compare CT findings with those from other imaging techniques; and 3) to assess whether CT can help to diagnose tarsal pathology. Study design Retrospective case series. Methods Computed tomography of the tarsus was performed on 15 horses (n = 17 joints) with tarsal lameness. The horses were divided into 3 groups depending on the reason for CT examination, as follows: 1) other imaging techniques were inconclusive; 2) evaluation of a fracture; or 3) other imaging techniques showed tarsal lesions, and CT was performed to assess whether additional lesions were present. Results Group 1 included 7 horses. Lesions detected with CT included subchondral cyst‐like lesions (2 horses); an osteolytic lesion in the cochlea tibiae (one horse); degenerative changes of the distal tarsal joints (2 horses); osteolytic lesions tarsometatarsal joint (one horse); and sclerosis of the third tarsal bone with a lesion of the tarsometatarsal interosseous ligament (one horse). In this group, CT provided information on the character and extent of the lesion that was not available with other imaging techniques. Computed tomography revealed more information about the extent and complexity of the fracture than radiography in Group 2, whereas CT did not provide extra information in Group 3. Conclusions Focal lesions located between the tarsal bone surfaces are difficult or even impossible to detect with radiography and ultrasonography, but they can be detected and characterised with CT. Potential relevance Computed tomography of the tarsus should be considered when radiography and ultrasonography are inconclusive, or for further evaluation of tarsal fractures. The Summary is available in Chinese – see Supporting information.